ANALISIS PENENTUAN HARGA JUAL DENGAN METODE COST PLUS PRICING DAN PENGARUHNYA TERHADAP LABA YANG DIHASILKAN PADA UD MAJU - sari, yunita (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2018)
ABSTRACTCost plus pricing method with full costing approach is one of the many methods used by the company in determining the selling price because it is considered as an easy method to understand. Cost plus pricing method with full costing approach also take into account all expenses incurred to produce a product either variable cost or fixed cost. The purpose of this research is to help UD Maju in determining the selling price and to know the amount of profit obtained by UD Maju during January 2018. This research was conducted on one of Small Medium Enterprises which is UD Maju which is located at Jalan Titi Papan Gang Pemuda, Sei Sikambing D , Medan managed by Mr. Suparman. The type of data used is primary data that is data obtained through observation and interview. Data analysis method used is descriptive quantitative that is managing data in the form of numbers. Based on the results of the research note that UD Maju has not done the calculation of cost of production and selling price. The selling price set by UD Maju is smaller than the selling price calculated using cost plus pricing method with full costing approach. From the results of the study, it can be concluded that during this UD Maju suffered losses Keywords: Cost Plus Pricing, Full Costing, Selling Price, Profit.